Solid Waste and Environmental Impacts on Highways: Mapeamento sistemático da literatura - Arana, Alba Regina Azevedo; Silva , Paulo Antônio da; Uliana, Maíra Rodrigues; Silva, Ivan Ricardo Aguilar da (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Highways are integrated into the physical, biotic, and socioeconomic context, which is fundamental for proposing corrective actions that ensure balanced coexistence with the environment. This article aims to construct a critical reflection on solid waste and environmental impacts and draw a parallel with the presence of solid waste on highway SP-613 in Morro do Diabo State Park. The method consisted of a Systematic Literature Mapping (SLM) and textual analysis on solid waste and environmental impacts in electronic databases. This research was approved by the Research Ethics Committee under no. 4201. The publication survey reached a total of 551 references for articles in English and 105 in Portuguese. After applying exclusion criteria, 200 and 29 references were retained, respectively. Textual analysis revealed differences in thematic approaches. The impact of highways as environments for the propagation of waste due to transportation and the presence of landfills is highlighted. The SLM allowed establishing a situational diagnosis of the main publications, pointing out the actions of prevention, mitigation, and compensation of environmental damages that can affect the environmental and socioeconomic balance resulting from the disposal, management, transportation, deposition, and/or reuse of solid waste.
Keywords: Systematic Analysis; Environmental Impact; Pontal do Paranapanema; Morro do Diabo State Park